Uma Lulik as Heritage: Authorised Heritage Discourse in Timor-Leste - Carolina Boldoni (e-cadernos ces)
Timor-Leste has endured different foreign presences: the Portuguese colonisation (1515-1974), the Indonesian military occupation (1974-1999) and, since the restoration of the national independence (2002) which has been defined the “NGOs invasion” (Brunnstrom, 2003). These different governances have produced various Authorised Heritage Discourses – AHD (Smith, 2006) whose echoes are traceable in the current national AHD. This paper, based on 15 months of ethnographic fieldwork, shows the entanglements between the previous colonial AHDs and the current one in Timor-Leste, in regard to ancestral houses (uma lulik). The aim is to examine heritage as a historical process by showing how the current post-colonial AHD is affected by the inference of the past and colonial perspectives on the local heritage, producing and reproducing neo-colonial governmentalities.